Oregon primary care providers as a frontline defense in the War on Melanoma™: improving access to melanoma education - Becker, Alyssa L.; Nelson, Jacob H.; Verdieck-Devlaeminck, Alex; Berry, Elizabeth G.; Orfaly, Victoria E.; Stoos, Elizabeth R.; Tran, Jessica; Latour, Emile; Sahni, Vikram N.; Xu, Shuai; Babcock, Megan; Bar, Anna; et al. (Frontiers in Medicine, 2025)
Melanoma is one of the deadliest forms of skin cancer but is typically cured with surgical excision when detected early. As an access point to medical care, primary care providers (PCP) play an integral role in early skin cancer detection. However, limited time for examinations and dermatologic training may present barriers to effective skin examination in the primary care setting. As a facet of Oregon Health & Science University’s War on Melanoma™ (WoM), our multi-pronged outreach initiative aims to provide PCPs across Oregon with free, convenient, and effective melanoma education. The WoM PCP education campaign was disseminated starting in May 2019 through primary care networks throughout the state of Oregon to 12,792 PCPs, and education was delivered across several platforms: online multimedia tools, large group didactics, individualized practice-based sessions, and in-person distribution of materials to clinics. To date, 829 PCPs have participated in the online Melanoma Toolkit for Early Detection curriculum, 1,874 providers have attended CME didactics, and 9 clinics have received facilitated meetings by Oregon Rural Practice-based Research Network. Eighty-three clinics (comprising 770 providers) were visited on-site and provided educational materials, and more than 150 PCPs have received a free smartphone dermatoscope to aid in skin examination and e-consultation. OHSU’s WoM has successfully implemented a multifaceted approach to provide accessible melanoma education to PCPs across the state of Oregon. As a result, we hope to encourage appropriate skin examination in the primary care setting and improve PCPs’ diagnostic accuracy and confidence in pigmented lesion evaluation.